滴水穿石：某偏鄉國中駐校心理諮商介入方案之縱貫性追蹤研究 A Six-Year Counseling Program for Remote Junior High School Students: A Follow-Up Outcome Study - 林淑君 Shu-Chun Lin; 王麗斐 Li-Fei Wang (National Taiwan Normal University, 2015)
本研究旨在探討某企業贊助諮商心理師進入偏鄉國中進行駐校諮商服務方案之經驗與成效，本方案已進行6 年並持續進行中。本研究針對100 學年度畢業班學生（共10 人）進行縱貫性追蹤研究，探討他們在國中就讀期間接受駐校諮商方案的成效，並於其畢業後持續追蹤。資料蒐集方式包括：於該班學生七年級下學期期末、八年級下學期期末（四人受訪，兩男、兩女）、九年級畢業前（10 人受訪，五男、五女）及畢業後1 年暑假（五人受訪，兩男、三女）進行訪談；以及後續的追蹤關懷（Facebook、Line、電話、寒暑假聚會等等），並佐以教師訪談及本方案諮商心理師之工作記錄。研究結果發現，此一長期駐校諮商服務方案對學生最顯著之效益在於：一、不放棄、堅持下去態度的養成；二、情緒表達與人際互動技巧的提升。研究結果顯示，這些畢業生進入高職／專科後，雖然在人際與學業適應仍遭遇困難，然而，他們學會堅持下去、不放棄，顯現此方案對該校學生具有長期性影響，促使學生內在改變，形成保護他們不放棄的支持力量。最後研究者提出對本方案的省思與未來對偏鄉青少年介入之建議。 The purpose of this study was to explore the outcomes of a six-year counseling program sponsored by an enterprise for remote junior high school students. Ten students (five males, five females) participated in the study whom participated in the counseling program three years and already graduated from the junior high school three years. The results showed that the counseling program had long-term effects on these students. They had learned how to regulate their emotions and social skills, and to adopt a "never give-up" attitude from the counseling program and applied them into their life after graduation. The results and suggestions for further research and practice are discussed in this paper.